STRATEGI KOMUNIKASI MEDIA SOSIAL INSTAGRAM INDOMARET DALAM MEMBANGUN BRAND AWARENESS - Rama Febriero Pradana Wahyudiputra; Sri Dewi Setiawati (Indonesian Journal of Digital Public Relations (IJDPR), 2023)
PT. Indomarco Prismatama is one of the pioneers of retail in Indonesia, which was established in 1988. Since being franchised in 1997, it is a pioneer in the modern store retail franchise business. In 1997 Indomaret expanded its first franchise minimarket business in Indonesia after having more than 230 minimarket outlets. The purpose of this study is to determine the Brand Awareness built by PT. Indomarco Prismatama in terms of the purpose of doing Instagram social media account credibility, content management, and building interactions on Instagram social media accounts. This study uses a qualitative approach with case study methods on Instagram accounts of PT. Indomarco Prismatama to describe and explore the Brand Awareness phenomenon that occurred at PT. Indomarco Prismatama. This research was conducted by referring to the concepts and theories, namely The Circular Model of Some (Regina Lutrell, 2015), the Brand Awareness pyramid (Durianto, 2004). The conclusion of this study is that content management at PT. Indomarco Prismatama applies The Circular Model of Some in its content creation so that it can focus on the message, customer, and context. And also so that the content can provide benefits to the community. Keywords: brand awareness, content management, Instagram, social media